Case Report: Bortezomib Plus CDOP Followed by Sequential Autologous Hematopoietic Stem Cell Transplantation and Lenalidomide-Based Maintenance Therapy in Plasmablastic Lymphoma - Cai, Jiao; Qiu, Ling; Ma, Lei; Zhang, Nan; Fan, Fang-yi (Frontiers in Medicine, 2021)
The standardized treatment plan for patients with plasmablastic lymphoma (PBL) remains controversial. Taking morphological characteristics and immunophenotypes into consideration may provide superior options for the treatment of PBL. In this case, we report that a myeloma-type regimen containing bortezomib plus cyclophosphamide, epirubicin, vindesine and prednisolone (CDOP) followed by sequential autologous hematopoietic stem cell transplantation (ASCT) and lenalidomide-based maintenance therapy to treat PBL may represent a promising regimen to improve the prognosis.